2018
DOI: 10.1097/pap.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Extraneuraxial Hemangioblastoma: Clinicopathologic Features and Review of the Literature

Abstract: Extraneuraxial hemangioblastoma occurs in nervous paraneuraxial structures, somatic tissues, and visceral organs, as part of von Hippel-Lindau disease (VHLD) or in sporadic cases. The VHL gene plausibly plays a key role in the initiation and tumorigenesis of both central nervous system and extraneuraxial hemangioblastoma, therefore, the underlying molecular and genetic mechanisms of the tumor growth are initially reviewed. The clinical criteria for the diagnosis of VHLD are summarized, with emphasis on the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 194 publications
0
34
0
Order By: Relevance
“…Recently, increased attention has been paid to extraneural hemangioblastomas. 2,4,5 To our knowledge, there have been 24 cases of sporadic renal hemangioblastomas reported in the English literature. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The clinical characteristics of previously reported cases, with those of the three cases in the current study, are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, increased attention has been paid to extraneural hemangioblastomas. 2,4,5 To our knowledge, there have been 24 cases of sporadic renal hemangioblastomas reported in the English literature. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The clinical characteristics of previously reported cases, with those of the three cases in the current study, are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…These masses could easily be misdiagnosed as clear cell RCC or angiomyolipoma. Interestingly, Bisceglia et al 2 found that most cases reported in the literature were from the Far East, and the authors considered that there might be an unknown genetic feature common to members of a particular ethnic or racial group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemangioblastomas are benign tumors that are either sporadic or associated with Von Hippel-Lindau disease (VHLD). [3] e most hemangioblastomas occur in the cerebellum or the medulla oblongata with only a minority occurring within the spinal cord (i.e., 7-10% intramedullary). [4] Purely extradural hemangioblastomas are extremely rare.…”
Section: Introductionmentioning
confidence: 99%